(untitled) (Fiep Bulletin - online, 2011)
Disorder and Attention Deficit Hyperactivity Disorder-ADHD is a persistent pattern of inattention and / or hyperactivity-impulsivity more frequent and severe than that typically observed in children of an equivalent level of development. Objective To investigate evidence of ADHD in females in the band in elementary school,the city of Macapa. . Material and Methods This study was conducted in four public schools, selectedrandomly, in a universe of 342 children, female, aged 7 to 10 years. This study used the DSM IV diagnostic criteria applied to teachers and parents of children. For data analysis we used the frequency distribution for the variables qualitativas.Teste Chi square test to compare qualitative variables, and using the statistical package BioEstat 5.0, Ayres (2007) for the treatment of the data that were presented in the form of tables.Results you can see the occurrence of 42 framed in the diagnostic criteria of ADHD among the children investigated in the four schools of research, 71.4% in the age group 90 to 10 years still can be seen that only the type of ADHD, Predominantly combination is that no statistical difference between age groups, corresponding to 77.8%., followed by 68.2% of the Predominantly Inattentive type. Conclusion The firstobservations were made more frequently in the school environment by teachers who realize the difficulties in social interaction of the child. Parents do not always able to understand and accept the differences in behavior of their daughters.